Microtubule Motor Transport of Organelles in a Specialized Epithelium: The RPE - Hazim, Roni A.; Williams, David S. (Frontiers in Cell and Developmental Biology, 2022)
The retinal pigment epithelium (RPE) is a uniquely polarized epithelium that lies adjacent to the photoreceptor cells in the retina, and is essential for photoreceptor function and viability. Two major motile organelles present in the RPE are the melanosomes, which are important for absorbing stray light, and phagosomes that result from the phagocytosis of the distal tips of the photoreceptor cilium, known as the photoreceptor outer segment (POS). These organelles are transported along microtubules, aligned with the apical-basal axis of the RPE. Although they undergo a directional migration, the organelles exhibit bidirectional movements, indicating both kinesin and dynein motor function in their transport. Apical melanosome localization requires dynein; it has been suggested that kinesin contribution might be complex with the involvement of more than one type of kinesin. POS phagosomes undergo bidirectional movements; roles of both plus- and minus-end directed motors appear to be important in the efficient degradation of phagosomes. This function is directly related to retinal health, with defects in motor proteins, or in the association of the phagosomes with the motors, resulting in retinal degenerative pathologies.